Passive gripper inspired by Manduca sexta and the Fin Ray® Effect. (26th July 2017) - Crooks, Whitney; Rozen-Levy, Shane; Trimmer, Barry; Rogers, Chris; Messner, William
Soft robotic grippers are advantageous for tasks in which a robot comes into close contact with a human, must handle a delicate object, or needs to conform to an object. Most soft robotic grippers, like their hard counterparts, require actuation to maintain a grip on an object. Here, we present a passive, soft robotic gripper that requires power to open and close but not to maintain a grip, which can be problematic in environments with limited energy availability (e.g. solar or battery power). Passive grip, by not requiring power to maintain grip on an object, provides a unique and safe alternative to energy-limited or energy-scarce environments. The Tufts Passive Gripper was inspired by the passive grip of the Manduca sexta and the simplicity of the Fin Ray® Effect. The gripper can be three-dimensional printed as one part on a multimaterial three-dimensional printer and only requires four additional steps to install the motor/tendon actuation mechanism. The gripper was capable of picking up over 40 common household objects, including a tissue, a pen, silverware, a needle, a stapler, a cup, and so on. The maximum load a gripper could hold when oriented perpendicular and parallel to the ground was 530 g (1 lb) and 240 g (0.5 lb), respectively.